The Influence of Transport Parameters and Enzyme Kinetics of the Fibrinolytic System on Thrombolysis: Mathematical Modelling of Two Idealised Cases - Zidanšek, A; Blinc, A (Thrombosis and Haemostasis, 1991)
Experimental data obtained by magnetic resonance imaging and photographing clot dissolution in vitro have shown that whole blood clots dissolve almost two orders of magnitude faster when urokinase is introduced into the clot by pressure induced permeation than when its access is limited to diffusion. In view of these findings, two mathematical models have been developed that quantitatively link the enzymatic and transport properties of the fibrinolytic system to the velocity of thrombolysis. Without a pressure gradient across the thrombus, the plasminogen activator molecules diffuse into the thrombus through the blood-thrombus boundary plane. The blood-thrombus boundary slowly moves inwards due to thrombolysis that is spatially restricted to a relatively narrow zone. The velocity of thrombolysis is primarily limited by the diffusion constants of the plasminogen activator and plasmin. In contrast, when plasminogen activator is rapidly distributed along the thrombus by pressure induced bulk flow, lysis occurs at each segment of the thrombus after a lag period that is due to plasmin activation and sufficient fibrin degradation. The lag time is determined primarily by the catalytical properties of the plasminogen activator and plasmin. The mathematical models with the observations of the clot boundaries during lysis permit the characterization of plasmin action on the fibrin network.